2019
DOI: 10.7759/cureus.4994
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible Electroporation For Liver Tumors: A Review Of Literature

Abstract: The prevalence of liver tumors is increasing worldwide. These can be broadly classified into primary and secondary types, depending upon the origin of the tumor. Multiple modalities are available for the management of these tumors. Ablative techniques are becoming the cornerstone of management especially for the tumors which are unresectable. Thermal ablative techniques include radiofrequency ablation (RFA), microwave ablation (MWA), and cryotherapy. Recently, a non-thermal technique known as irreversible elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…It has been reported to particularly mitigate the risk of bile duct strictures and biliary fistula formation, which have been reported following use of thermal ablative techniques near biliary strictures 3 9. IRE is considered particularly efficacious as an intervention for small liver tumours (≤4 cm in diameter) 11. Reviews of small retrospective series have reported IRE producing complete responses in up to 90% of tumours and partial responses in 10% of tumours 10 11…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported to particularly mitigate the risk of bile duct strictures and biliary fistula formation, which have been reported following use of thermal ablative techniques near biliary strictures 3 9. IRE is considered particularly efficacious as an intervention for small liver tumours (≤4 cm in diameter) 11. Reviews of small retrospective series have reported IRE producing complete responses in up to 90% of tumours and partial responses in 10% of tumours 10 11…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that modern devices are synchronized to the electrocardiogram (ECG) of the patient to deliver pulses in the refractory period of the cardiac contraction to avoid this complication. Other potential complications are hepatic abscesses, pneumothorax, bleeding, portal vein thrombosis and bile duct leakage or occlusion [ 124 , 126 ]. Needle tract seeding following IRE was also described [ 127 ].…”
Section: Local Ablative Therapiesmentioning
confidence: 99%
“…IRE is a modality in which high electric field strength is focused to ablate prostate tissues. The electric fields between two monopolar electrodes inserted into tissues cause tissue ablation, including the generation of irreversible nano-sized pores on the surfaces of cell membranes 9 . These irreversible pores cause cells to undergo either catabolic or anabolic apoptosis, followed by necrosis 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other focal therapies, this property of IRE can preserve blood vessels and neurons surrounding cells, killing only the involved cells. Thus, one important advantage of IRE is the rapid recovery from injury 9 , 11 , 12 . Because the prostate is located far from the heart, IRE can be used to ablate prostate cancer tissues, while avoiding its heart-associated drawbacks, including muscle contraction and arrhythmia 12 .…”
Section: Introductionmentioning
confidence: 99%